Editorial - Forrest, Michelle (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
This special issue of Paideusis contains refereed papers from the Conference on Open-mindedness and the Virtues in Education held in honour of William Hare at Mount Saint Vincent University, October 2-4, 2008, on the occasion of Dr. Hare’s retirement from full-time teaching.